Fluorescent magnetic iron oxide nanoparticles for cardiac precursor cell selection from stromal vascular fraction and optimization for magnetic resonance imaging - Verma VK (Dove Medical Press, 2015)
Vinod Kumar Verma,1 Suguna Ratnakar Kamaraju,1 Ravindranath Kancherla,1 Lakshmi K Kona,1 Syed Sultan Beevi,1 Tanya Debnath,1 Shalini P Usha,1 Rammohan Vadapalli,2 Ali Syed Arbab,3 Lakshmi Kiran Chelluri11Department of Transplant Biology, Immunology and Stem Cell Laboratory, Global Hospitals, 2Department of Imageology, Vijaya Radiology Centre, Hyderabad, India; 3Department of Biochemistry and Molecular Biology, Georgia Regents University, Augusta, GA, USAAbstract: Fluorescent magnetic iron oxide nanoparticles have been used to label cells for imaging as well as for therapeutic purposes. The purpose of this study was to modify the approach to develop a nanoprobe for cell selection and imaging with a direct therapeutic translational focus. The approach involves physical coincubation and adsorption of superparamagnetic iron oxide nanoparticle-polyethylene glycol (SPION-PEG) complexes with a monoclonal antibody (mAb) or a set of antibodies. Flow cytometry, confocal laser scanning microscopy, transmission electron microscopy, iron staining, and magnetic resonance imaging were used to assess cell viability, function, and labeling efficiency. This process has been validated by selecting adipose tissue-derived cardiac progenitor cells from the stromal vascular fraction using signal regulatory protein alpha (SIRPA)/kinase domain receptor (KDR) mAbs. These markers were chosen because of their sustained expression during cardiomyocyte differentiation. Sorting of cells positive for SIRPA and KDR allowed the enrichment of cardiac progenitors with 90% troponin-I positivity in differentiation cultures. SPION labeled cardiac progenitor cells (1×105 cells) was mixed with gel and used for 3T magnetic resonance imaging at a concentration, as low as 12.5 µg of iron. The toxicity assays, at cellular and molecular levels, did not show any detrimental effects of SPION. Our study has the potential to achieve moderate to high specific cell selection for the dual purpose of imaging and therapy.Keywords: noninvasive molecular imaging, PEGylated nanoprobe, cardiomyocyte, cytotoxicity, apoptosis